Somatic embryogenesis in Abutilon indicum (L.) Sweet and assessment of genetic homogeneity using SCoT markers. (4th July 2017) - Seth, S.; Rath, S. C.; Rout, G. R.; Panigrahi, J.
Abstract: This study describes an efficient plant regeneration protocol for Abutilon indicum via somatic embryogenesis from 2, 4-dichlorophenoxyacetic acid (2, 4-D)-induced leaf-derived callus on MS medium, fortified with 13.32 μM 6-benzyladenine (BA), 2.68 μM α-naphthalene acetic acid (NAA), 200 mgl −1 -activated charcoal, and 11.54 μM ascorbic acid. This combination produced the highest (15.5 ± 0.7) number of somatic embryos after four weeks of culture. Further, the embryogenic calli were transferred to MS medium supplemented with 13.32 μM BA, 1.44 μM gibberellic acid (GA3 ), and 3% (w/v) sucrose and showed highest rate of germination (76.3 ± 7.0%). The germinated somatic embryos showed maximum plantlet conversion (62.6 ± 1.90%) on ½ MS medium supplemented with 4.92 μM indole-3-butyric acid and 6.0% sucrose (w/v). The highest frequency of secondary somatic embryogenesis (34.4 ± 0.82) was observed on ½ MS medium, supplemented with 133 μM FeSO4 ·7H2 O, 74 μM ethylene diamine tetraacetic acid disodium dihydrate (disodium EDTA), and 15% polyethylene glycol-4000 (PEG-4000) after three weeks of subculture. Scanning electron microscopy observations also substantiated the development of primary and secondary somatic embryos from embryogenic calli. Start codon targeted polymorphism (SCoT) marker analysis of 214 somatic embryo-derived plantlets amplified 167 numbers of bands ranging from 230 to 2125 bp. The homogeneous banding pattern confirmed the genetic uniformity of this sample of somatic embryo-derived plantlets as compared with the donor plant.